Parallel Learning Reinforcement-A Case Study - Jayanthi, S.; Renuka, T.; Shekar, G. N. (Journal of Engineering Education Transformations, 2015)
Even though Mathematics, the queen of all sciences, is necessary for the engineers to master, their basic knowledge in mathematics, before taking the first year course is crucial. There is an urgent need for strengthening the students’ fundamentals in mathematics, especially that of the fresh entrants into the engineering course. A novel methodology consisting of identifying those students with poor comprehension, coaching them during extra hours along with the regular course, improving their caliber and evaluating their performance to quantify the success of the process was carried out successfully in the department of mathematics, BMS College of Engineering. The result of the student’s survey is discussed in this paper.